The Triggers of Learning Loss in Online Learning in German Language Education Study Program, Universitas Negeri Malang - Oryza Kumala Putri; Primardiana Hermilia Wijayati (Nexus Publishing, 2024)
This research is motivated by the results of analysis and interviews with lecturers of the German Language Education Study Program, State University of Malang. It was found that the phenomenon of learning loss has occurred among students as indicated by the decline in knowledge and skills at the beginning of offline learning. This study aims to describe the factors that can cause learning loss in students during online learning. Identification of the learning loss phenomenon was conducted so that lecturers and students can develop strategies to overcome gaps in learning materials. Learning loss is a phenomenon of decreased knowledge and skills. The phenomenon occurs due to sudden changes in learning. This research employed a descriptive analysis method with a quantitative approach. The sampling technique used Purposive Random Sampling, with a research sample of students from 2019-2021 batch. The students were from three classes recruited randomly. Data was obtained using an online questionnaire distributed using Google Form. The results identified the lack of interaction between students and lecturers as well as students and students, the lack of distribution of internet networks as a facility factor, students' independent learning style, and the less supportive home environment for online learning during the COVID-19 pandemic. In conclusion, most students of the German Language Education Study Program have encountered the factors that cause the phenomenon of learning loss.